Survival after oxaliplatin therapy of irinotecan-pretreated advanced colorectal cancer patients - Melichar, Bohuslav; Kohlová, Tereza; Vesely, Pavel (Hepato-gastroenterology, 2005)
BACKGROUND/AIMS: The activity of oxaliplatin (OHP) and irinotecan (CPT) alone or in combination with 5-fluorouracil (5-FU) in advanced colorectal cancer is comparable, but there are limited data on the effectiveness of oxaliplatin in patients pretreated by irinotecan. METHODOLOGY: We have analyzed retrospectively the survival of 77 consecutive advanced colorectal cancer patients treated with OHP after previous CPT therapy. Multivariate analysis was performed by Cox regression method, with the results expressed as hazard ratio (HR). RESULTS: The median survival from the start of OHP therapy was 10.7 months (1-year survival 43%). The median survival was not reached in 10 patients treated by hepatic arterial infusion of OHP (>10.6 months). The median survival from the diagnosis of advanced/metastatic disease was 34.3 months. On multivariate analysis, hemoglobin <125g/L (HR=2.42), neutrophils <5200 per microL (HR=0.36), duration of advanced/metastatic disease <21 months (HR=2.40) and interval from last CPT administration <3 months (HR=0.27) were statistically significant (p<0.05) independent predictors of survival from the start of OHP treatment, but only hemoglobin (HR=2.07), neutrophils (HR=0.32) and CEA <100microg/L (HR=0.44) were independent predictors of survival from the last CPT. There were 4 treatment-induced deaths after combination of OHP and raltitrexed (TOMOX). CONCLUSIONS: More than 40% of patients pretreated by irinotecan survived 1 year after start of OHP therapy. The therapy was similarly effective as a second or higher line of treatment. Hemoglobin levels and neutrophil count were independent factors associated with survival. The number of toxic deaths observed after TOMOX is alarming.
Keywords: rozvrh dávkování léků; Analysis of Variance; kolorektální nádory; vztah mezi dávkou a účinkem léčiva; Palliative Care; hodnocení rizik; Female; kamptothecin; Fluorouracil; multivariační analýza; paliativní péče; výsledek terapie; ženské pohlaví; Neoplasm Recurrence, Local; Oxaliplatin; Multivariate Analysis; Colorectal Neoplasms; Time Factors; časové faktory; lidé; Survival Analysis; staging nádorů; Drug Administration Schedule; Probability; Treatment Outcome; následné studie; Risk Assessment; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; organoplatinové sloučeniny; oxaliplatin; pravděpodobnost; retrospektivní studie; Dose-Response Relationship, Drug; analýza rozptylu; proporcionální rizikové modely; Follow-Up Studies; Male; fluoruracil; lokální recidiva nádoru; irinotekan; analýza přežití; Organoplatinum Compounds; Camptothecin; mužské pohlaví; Irinotecan; Retrospective Studies; Proportional Hazards Models; Neoplasm Staging; Humans